A Feasibility Study of Non-invasive Blood Glucose Level Detection Using Near-Infrared Optical Spectroscopy - Sridevi, Parama; Arefin, ASM Shamsul; Md Ibrahim, Abu Shahadat (Bangladesh Journal of Medical Physics, 2021)
Diabetes mellitus, a common disease of the modern era, is a glucose level disorder in the human body that affects the vital organs of the body and damages them gradually if left untreated. Regular blood glucose monitoring is one of the prescribed routines to control the complications of diabetes. Unfortunately, most available methods of blood glucose level measurement involve invasive ways. Invasive techniques are painful, make the finger skin calloused and the patients suffer from the risk of infectious diseases. Hence, there lies a need to develop an effective non-invasive blood sugar measurement technique to relieve the patients from the nuisance. In order to address the issue, a non-invasive technique has been designed and implemented using 940 nm near-infrared (NIR) LED and a corresponding photodiode. Initially, the in-vitro test was performed over the glucose solution of various concentrations to check the sensitivity of the device. After that pilot experiments were carried out on diabetic patients. The obtained results conformed the theory of near infra-red spectroscopic optical theory. The results also showed that the developed technique can be comparable with the conventional invasive glucometer based method. Furthermore, the implemented prototype is economically viable, especially for the low-income population. This promising results thus pledge the potentials, feasibility, and reliability of the NIR based non-invasive blood glucose detection devices. Bangladesh Journal of Medical Physics Vol.14 No.1 2021 P 1-13